(3fgGjI GdEOQGc aj OQGjI GdCadGcs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3GdHGH GdChdi ai GdebOeGJ GdChdi Gf GdJhUd Edi eYQaI YXe GdGLQGe GdSeGhjI hebGOjQ CHYGOgG Yf GdGQV def GYLH GdGTjGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG CTcGds
(3JfbU ef BNQgG hBNQ GdehLhO efgG eJab eY BNQ GdfSNI GdChdi LGeY GdHGTG (B- (3GdehUd (B368s
(3fSNI KGfjIHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B274 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B296 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs